Sustainable construction materials : copper slag - Dhir, Ravindra K.; Brito, Jorge de; Mangabhai, R. J.; Lye, Chao Qun (Woodhead Publishing series in civil and structural engineering., 2018)
Sustainable Construction Materials: Municipal Incinerated Bottom Ash discusses the global use of virgin aggregates and CO2 polluter Portland cement. Given the global sustainability agenda, much of the demand for these two sets of materials can be substantially reduced through the appropriate use of waste materials, thereby conserving natural resources, energy and CO2 emissions. Realistically, this change can only be realized and sustained through engineering ingenuity and new concepts in design. Although a great deal of research has been published over the last 50 years, it remains fragmented and ineffective. This book develops a single global knowledge-base, encouraging greater use of selected waste streams. The focus of massive systematic reviews is to encourage the uptake of recycled secondary materials (RSM) by the construction industry and guide researchers to recognize what is already known regarding waste.